The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00006324-200009000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Three-Point Vernier Alignment or Acuity Test as a Function of Age: Measurement Extended to Ages 5 to 9 Years

Abstract: The three-point Vernier alignment (or acuity) test was conducted on children from 5 to 9 years old. There is a significant difference between the 5-9 year old subjects and those in age groups 10 to 19 and 20 to 29 years in Vernier performance. These data were also compared with previously published data from older subjects (up to age 70). We conclude that Vernier function has not fully matured within the age range of 5 to 9 years; this finding is consistent with previous results reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…97 The development of positional acuity is likely dependent on development of cortical columns in striate cortex. 98 Alignment thresholds of typically developing children are not adult-like until 5 years of age 99 or later, 100,101 and have shown full maturation as late as age 14 years. 102 Other kinds of hyperacuity tasks, like the ability to detect minor perturbations in a circle, may not reach maturity until even later in life.…”
Section: Positional Acuitymentioning
confidence: 99%
“…97 The development of positional acuity is likely dependent on development of cortical columns in striate cortex. 98 Alignment thresholds of typically developing children are not adult-like until 5 years of age 99 or later, 100,101 and have shown full maturation as late as age 14 years. 102 Other kinds of hyperacuity tasks, like the ability to detect minor perturbations in a circle, may not reach maturity until even later in life.…”
Section: Positional Acuitymentioning
confidence: 99%
“…After instruction, at each gap tested, 10 determinations were made. High and low readings in a data set were dropped, and the bias and precision for the remaining group of eight readings were determined (55,60,61,64,66,76,77). The twopoint vernier test display was presented first, and this was followed by the three-point vernier test display.…”
Section: Vernieracuity or Alignment: Backgroundmentioning
confidence: 99%
“…Studies ofVeA as a function of age were conducted under a variety of conditions (56,57,60,76,77). A recent study of normal observers has shown that not only age, but also varying luminance, contrast, test stimuli sizes, test stimuli degradations, test distances (all within specific parametric ranges) do not significantly alter outcomes ifthe individual points of light do not overlap, and these stimuli are presented at superthreshold levels (66).…”
Section: Vernieracuity or Alignment: Backgroundmentioning
confidence: 99%
“…First, many experimental procedures for measuring visual interpolation are well suited for testing children and atypical populations because they are easy to understand. One common interpolation task is the three-point Vernier alignment task, which is used to efficiently assess retinal and cortical impairments in children (Kim, Enoch, Fang, Lakshminarayanan, Kono, Strada & Srinivasan, 2000), older adults (Yebra-Pimentel Vilar, Giraldez-Fernandez, Enoch, Lakshminarayanan, Knowles & Srinivasan, 1995) and clinical populations (Fang, Enoch, Lakshminarayanan, Kim, Kono, Strada & Srinivasan, 2000). In this task, observers are asked to judge the position of a central dot relative to flanking dots (see Fig.…”
Section: Introductionmentioning
confidence: 99%